Micronucleus test in peripheral blood of rats treated with hyperbaric oxygen after subtotal splenectomy preserving the lower pole - Paulo,Marcela Souza Lima (2015)
PURPOSE: To assess the mutagenic potential of the oxygen inhalation therapy (HBO), by means of the micronucleus test, performed in peripheral blood of rats that underwent subtotal splenectomy with lower pole preservation (ESTPI), after HBO sessions or simulations.METHODS: Eighteen male Wistar rats, were distributed into three groups of six animals: group 1 - submitted to ESTPI and HBO sessions; group 2 - submitted to ESTPI and HBO simulations; group 3 - underwent cyclophosphamide administration. In groups 1 and 2, blood samples from the animals' tails were collected before surgery (T0) and immediately after the 13th HBO session or simulation (T1). In group 3, tail blood samples were collected from animals before (T0) and 24 hours after (T1) cyclophosphamide (CP) delivery. The number of micronucleated normochromatic erythrocytes (MNNCE) was determined by blind counting 2000 normochromatic erythrocytes (NCE) per animal.RESULTS:Micronuclei average after CP delivery in group 3 was higher than before its use, thus confirming the mutagenic activity of this drug (p=0.01). In groups 1 and 2, no significant difference in the average of Micronuclei was observed when comparing it to blood samples before and after the 13th HBO session or simulation.CONCLUSION: The treatment protocol used in this study did not induce Micronucleus formation in animals submitted to ESTPI and HBO treatment or simulation.